2008
DOI: 10.1074/jbc.m803493200
|View full text |Cite
|
Sign up to set email alerts
|

A Ubiquitin-Proteasome Pathway for the Repair of Topoisomerase I-DNA Covalent Complexes

Abstract: Reversible topoisomerase I (Top1)-DNA cleavage complexes are the key DNA lesion induced by anticancer camptothecins (e.g. topotecan and irinotecan) as well as structurally perturbed DNAs (e.g. oxidatively damaged DNA, UV-irradiated DNA, alkylated DNA, uracil-substituted DNA, mismatched DNA, gapped and nicked DNA, and DNA with abasic sites). Top1 cleavage complexes arrest transcription and trigger transcription-dependent degradation of Top1, a phenomenon termed Top1 down-regulation. In the current study, we hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
121
1
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(140 citation statements)
references
References 39 publications
(18 reference statements)
9
121
1
2
Order By: Relevance
“…We have further shown that these two pathways play distinctive roles in the activation of etoposide-induced DDR and signaling [14]. Notably, cellular activities in the TOP2cc-processing pathways have also been shown to be involved in converting TOP1cc into different forms of DNA lesions [12,13,[17][18][19][20][21]. Different from that of TOP2cc, TOP1 is linked covalently to the 3′ terminus of DNA single-stranded break (SSB) in TOP1cc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have further shown that these two pathways play distinctive roles in the activation of etoposide-induced DDR and signaling [14]. Notably, cellular activities in the TOP2cc-processing pathways have also been shown to be involved in converting TOP1cc into different forms of DNA lesions [12,13,[17][18][19][20][21]. Different from that of TOP2cc, TOP1 is linked covalently to the 3′ terminus of DNA single-stranded break (SSB) in TOP1cc.…”
Section: Introductionmentioning
confidence: 99%
“…The structural information [8][9][10] and recent studies on the roles of cellular activities and pathways for TOPcc-induced DDR [11][12][13][14][15][16] have suggested that the interactions between TOPcc and cellular activities, such as proteasomal degradation, might process DNA break embedded in the enzyme center into more detectable DNA lesions. These DNA lesions are differentially detected and then followed by the activation of various DDR.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] Chlorambucil readily forms mono-adducts (as well as some crosslinks) with dsDNA, 15 whereas camptothecin does not react with the DNA strand directly, but rather interfere with topoisomerase I activity by blocking the re-sealing of the DNA, which may eventually result in frank strand breaks. 16 Surprisingly, we find that sequence-targeted PNAs that can react covalently with the DNA helix exhibit a highly inhibitory effect on gene correction in nuclear extract and in a cell culture, extra-chromosomal assay. In contrast, a conventional triplex forming PNA (TFP) showed little or no effect on gene correction, whereas a PNA-camptothecin conjugate was found to stimulate gene correction events in nuclear extracts, but not in a cell culture assay.…”
Section: O N O T D I S T R I B U T Ementioning
confidence: 99%
“…Permanently stalled topo I/DNA complexes are tagged with ubiquitin for proteasomal degradation. 16 Thus, an increased concentration of ubiquitin could increase the rate of protein/DNA complex processing, thereby increasing the gene correction rate. Also, ubiquitin serves as modulator of several DNA repair mechanisms and consequently, increased concentrations of ubiquitin could increase the processing rates for these reactions.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
See 1 more Smart Citation